Cost-Effective Synthesis and Spectroscopic Characterization of Polyphenyl Amines - Khatoon, B.A.; Subhashchandran, K.P.; Gurjar, Chandralekha; Vijayalekshmy, K.S. (Asian Journal of Chemistry, 2010)
Polyanilines were chemically synthesized by one step polymerization of aniline using 3 different oxidants-ammonium persulphate, potassium iodate and hydrogen peroxide. Standard redox potentials and redox couples were studied. The samples were characterized by UV, FTIR, FT Raman spectroscopy, X-ray 13C NMR and conductivity of polyanilines.